Improving facial esthetics using miniscrews: a case report - Elie KHOURY (International Arab Journal of Dentistry (IAJD), 2013)
The number of patients seeking treatment to improve their facial attractiveness is increasing. Nowadays orthodontic patients are requiring solutions to problems such as a minor gummy smile, a protruded lip, a posterior rotated mandible or even an open naso-labial angle. These problems are rarely all combined in one case, as biprotrusive lips are opposed to an open naso-labial angle, and solving one problem could aggravate the other. In this case report we describe the treatment of a hyperdivergent pattern patient resulting in a posterior positioning of the mandible with lack of chin. The patient had also a dental biprotrusion creating protruded lips combined to an open naso-labial angle and a minor gummy smile. The treatment consisted in correcting the protruded lips with concern not to widen the naso-labial angle. The vertical control for the anterior chin rotation and the gummy smile correction were done using miniscrews.